Blue Carbon Potential of Mangrove Ecosystems in Jakarta Bay for Climate Change Mitigation - Dawi, Mario Raja Sani; Sulistiono, Sulistiono; Kamal, Mohammad Mukhlis (Marine Science Department Diponegoro University, 2025)
Mangrove ecosystems are crucial for sustaining tropical coastal environments and play a vital role in climate change mitigation through their capacity to sequester and store blue carbon in both vegetation and sediment. Despite their ecological value, mangroves in Jakarta Bay are under increasing pressure from coastal development, land conversion, pollution, and unsustainable exploitation. These anthropogenic threats reduce mangrove cover and diminish their ability to function as carbon sinks. This study examined mangrove carbon stocks at four locations Muara Village, Kapuk Muara, Marunda, and Muara Jaya Village through vegetation surveys, biomass measurement, and the calculation of the Important Value Index (IVI) to analyze species composition and dominance. The results demonstrated considerable variation in biomass and carbon reserves across sites. Muara Village recorded the highest biomass (558.72 tons ha⁻¹) and carbon stock (262.59 tons ha⁻¹), followed by Kapuk Muara (411.18 tons ha⁻¹), Muara Jaya (365.39 tons ha⁻¹), and Marunda, which had the lowest values (208.9 tons ha⁻¹). Dominant species included Rhizophora mucronata and Avicennia marina, reflecting their ecological adaptability and contribution to blue carbon storage. The findings emphasize that mangrove areas with higher biomass and carbon reserves are critical for maintaining ecosystem resilience in Jakarta Bay. Conservation and restoration should therefore prioritize sites with strong carbon storage potential, while degraded areas require rehabilitation to enhance ecological services. Strengthening mangrove management will not only support biodiversity and coastal protection but also contribute significantly to regional climate change mitigation strategies through the preservation of blue carbon.